Aplikasi Multiple Clasification Analysis dalam Penentuan Faktor yang Mempengaruhi Gaji Dosen - Rosemarie Sutjiati Njotoprajitno (Jurnal Manajemen Maranatha, 2010)
The existence of high quality lecturer is a main condition on high quality education systems and practice. Almost every country in the world always develops the policy which support the existence of high quality lecturer. One of the policies which is supported by the government in many countries is the intervention policy which is directed to quality enhancement, to give sufficient welfare to the lecturers. With Multiple Classification Analysis Application in determination of factors which affect lecturer's salary, this research results are that the factors which affects the lecturer's salary significantly are academic position, sex and employment categories. It is hoped that this research will give understanding to the lecturers on the importance of academic stage administration which will results on the escalation of employment categories of the respective lecturers. This will also results on high quality lecturers.Keywords: Multiple Classification Analysis, salary, academic position, sex, employment categories